2011
DOI: 10.1002/dev.20612
|View full text |Cite
|
Sign up to set email alerts
|

Frontal EEG asymmetry and fear reactivity in different contexts at 10 months

Abstract: Individual differences in observed and maternal-rated fear behaviors and frontal electroencephalogram (EEG) asymmetry were examined in normally developing 10-month-old infants. EEG was recorded during resting baseline, as well as during stranger approach, mask presentation, and toy spider presentation. Mothers completed the Infant Behavior Questionnaire. For mask presentation, baseline and task right frontal EEG asymmetry as well as maternal ratings predicted fear behavior during the mask task. For stranger ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 42 publications
3
52
2
Order By: Relevance
“…Both FXS and control groups displayed escape behaviors most frequently, with similar levels of intensity across groups and ages. The prominence of escape behaviors in our sample is consistent with previous studies using a stranger episode with 9-month-old infants (Diaz & Bell, 2011). Despite the similar behavioral profiles of escape across FXS and TD groups, only the typical controls displayed an association of increased arousal with escape behavior.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both FXS and control groups displayed escape behaviors most frequently, with similar levels of intensity across groups and ages. The prominence of escape behaviors in our sample is consistent with previous studies using a stranger episode with 9-month-old infants (Diaz & Bell, 2011). Despite the similar behavioral profiles of escape across FXS and TD groups, only the typical controls displayed an association of increased arousal with escape behavior.…”
Section: Discussionsupporting
confidence: 91%
“…The stranger approach episode has been previously used with similar age groups to elicit behavioral variables (e.g., Aktar, Majdanzic, de Vente, & Bogels, 2012; Diaz & Bell, 2011; Kochanska, 1998). The stranger approach episode occurred at the same point in each child's assessment, directly following a nonstressful, engaging task.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of asymmetry at rest indicate that left (relative to right) frontal asymmetry is indicative of approach behaviors and expression of positive emotions, and right (relative to left) asymmetry is associated with avoidance behaviors and expression of negative emotions (e.g., Calkins, Fox, & Marshall, 1996; Fox & Davidson, 1984; Fox, Henderson, Rubin, Calkins, & Schmidt, 2001; Smith & Bell, 2010). Studies of asymmetry in response to stimuli have shown similar results, whereby individuals who are exposed to negative avoidance or withdrawal related emotional stimuli – such as those that induce feelings of sadness – respond with greater right (relative to left) asymmetry, but those exposed to approach and positive emotion stimuli show greater left (relative to right) asymmetry (e.g., Coan & Allen, 2003, 2004; Diaz & Bell, 2012; Killeen & Teti, 2012). …”
Section: Here and Now: Assessing Eeg Asymmetry In Real-time Interactionsmentioning
confidence: 83%
“…Power was computed for the 6 to 9 Hz frequency band, as infants at this age have a dominant frequency between 6 and 9 Hz (Bell & Fox, 1994; Marshall, Bar-Haim, & Fox, 2002). This particular frequency band is thought to approximate the alpha band in adults and has been used in previous studies of infant frontal asymmetry (e.g., Bell & Fox, 1994; Buss et al, 2003; Diaz & Bell, 2012; Fox et al, 1992; Fox et al, 2001; Smith & Bell, 2010). For the current study, EEG power was expressed as mean square microvolts and the data transformed using the natural log (ln) to normalize the distribution.…”
Section: Methodsmentioning
confidence: 99%